Experiential Outdoor Activities In Improving Students’ Vocabulary Achievement - Lustani Samosir (Institut Agama Kristen Negeri Tarutung, 2020)
This research is A Classroom Action Research held at SMP Negeri 4 Sipoholon in Academic Year 2018/2019. The problem of the research is; Does experiential outdoor activities significantly improve the students’ vocabulary achievement of the eight grade students at SMP Negeri 4 Sipoholon? And the objective is to find out whether experiential outdoor activities significantly improve the students’ vocabulary achievement. The subject of the research is 20 students of the eight grade students of SMP N. 4 Sipoholon in academic year 2018/2019. This research was only acted in one cycle in which, that in pre-test there was not student who got good and very good interpretation yet there are one who was fail and 8 students who were poor, in the minimum criterion used in the school is 70, so the researcher concluded that based on the students’ pre-test score they are fail. In fact based on the data analysis of the post-test that there are 11 students who got very good (80 – 100) and 9 students got good (66 – 79), and none of the students got fair (56-65), poor (40-55), and fail (39). It means all the students passed the minimum criterion applied in that school. On the other hand, it can be concluded that experiential out-activities significantly improves the students’ vocabulary mastery. Besides, by analyzing the data through t-test, it can be concluded that the mean of students’ post test score is higher than the mean of students’ pre-test score or 78.25 55.25. In addition, p-value under df (degree of freedom) is 19 or 1.729, it was found t-value has a significant different with t-table or 78.25 1.729. On the other hand, it can be said that the Ho (null hypothesis) is rejected and the Ha (alternative hypothesis) is accepted, in which there is a significant improvement of students’ vocabulary achievement taught by experiential outdoor activities. Keyword: Experiential Outdoor Activities, Students’ Vocabulary Achievement